The Only Exception: Teenage Pregnancy in the Philippines - Gregorio, Veronica (Review of Women's Studies; Vol 28 (2018): Review of Women's Studies Volume XXVIII (2018), 2023)
Teenage pregnancy rates across the Asia Pacific Region has declined over the past two decades, except in the Philippines. The alarming situation continues despite the effort of the Philippine government to pass laws and implement programs related to reproductive health. Drawing from feminist theory and through photo-elicitation, this paper explores how teenage mothers see and understand adolescent sexuality, romantic relationships, and motherhood. By capturing these realms from the perspective of the teenage mothers and locating it at the community level, the author presents a nuanced understanding of the previously established analyses on the causes and effects of teenage pregnancy in the Philippines.